NGO and Human Security: The Case of Human Initiative in Indonesia's Disaster Response: - Rifai, Maulana (SIYAR Journal, 2026)
Indonesia is geographically located within the disaster-prone pacific ring of fire, making it vulnerable to recurring natural disasters such as floods, earthquakes, and landslides. These disasters pose significant threats to human survival and well-being. The presence of Non-Governmental Organizations (NGOs) becomes crucial in advocating, educating, and assisting disaster victims, completing the government's efforts in ensuring human security. The concept of human security is a non-traditional approach which relies heavily on human being or community rather than state entity. This study explores the role of Human Initiative in disaster management and the challenges it faces, with a focus on human security. David Lewis and Nazneen Kanji theoretical framework guides the analysis in this study. They identify three key roles that NGOs play: implementers, catalysts, and partners. This study adopts a qualitative method with a case study approach through field observations and interviews. The findings reveal that Human Initiative plays an active, responsive, and collaborative role in disaster management in Indonesia by addressing both individual and environmental security. Its achievement depends on a comprehensive and sustainable approach involving all stakeholders, including government entities, the private sector, and community organizations.